23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

Correction to: Two adjacent phosphorylation sites in the C-terminus of the channel's α-subunit have opposing effects on epithelial sodium channel (ENaC) activity. - Diakov, Alexei; Nesterov, Viatcheslav; Dahlmann, Anke; Korbmacher, Christoph (Pflügers Archiv: European Journal of Physiology, 2022)
EVALuna2:505610

Elevated tissue sodium deposition in patients with type 2 diabetes on hemodialysis detected by 23Na magnetic resonance imaging - Kopp, Christoph; Linz, Peter; Maier, Carolin; Wabel, Peter; Hammon, Matthias; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Uder, Michael; Luft, Friedrich C.; Titze, Jens; Dahlmann, Anke (Kidney International, 2018)
Long-term elevated blood sugar levels result in tissue matrix compositional changes in patients with diabetes mellitus type 2 (T2DM). We hypothesized that hemodialysis patients with T2DM might accumulate more tissue sodium than control hemodialysis patients. To test this, 23Na magnetic resonance imaging (23Na MRI) was used to estimate sodium in skin and muscle tissue in hemodialysis patients with or without T2DM. Muscle fat content was estimated by 1H MRI and tissue sodium content by 23Na MRI pre- and post-hemodialysis in ten hemodialysis patients with T2DM and in 30 matched control hemodialysis patients. We also assessed body fluid distribution with the Body Composition Monitor. 1H MRI indicated a tendency to higher muscle fat content in hemodialysis patients with T2DM compared to non-diabetic hemodialysis patients. 23Na MRI indicated increased sodium content in muscle and skin tissue of hemodialysis patients with T2DM compared to control hemodialysis patients. Multi-frequency bioimpedance was used to estimate extracellular water (ECW), and excess ECW in T2DM hemodialysis patients correlated with HbA1c levels. Sodium mobilization during hemodialysis lowered muscle sodium content post-dialysis to a greater degree in T2DM hemodialysis patients than in control hemodialysis patients. Thus, our findings provide evidence that increased sodium accumulation occurs in hemodialysis patients with T2DM and that impaired serum glucose metabolism is associated with disturbances in tissue sodium and water content.
EVALuna2:34700

Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Friedrich, Anna Carolina; Linz, Peter; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Schiffer, Mario; Uder, Michael; Kopp, Christoph; Dahlmann, Anke (Kidney & Blood Pressure Research, 2022)
BACKGROUND: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. METHODS: In our observational study, 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-magnetic resonance imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by bioimpedance spectroscopy (BIS) and laboratory parameters were assessed. RESULTS: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units (a.u.), p < 0.01) and muscle tissue (21.5 ± 3.6 vs. 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, includingexcess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/mL, p < 0.05). CONCLUSION: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 23Na-magnetic resonance imaging; Cardiovascular disease; Hemodialysis; Tissue Na+

Modification of Dialysate Na+ Concentration but not Ultrafiltration or Dialysis Treatment Time Affects Tissue Na+ Deposition in Patients on Hemodialysis. - Kopp, Christoph; Kittler, Lukas; Linz, Peter; Kannenkeril, Dennis; Horn, Stephan; Chazot, Charles; Schiffer, Mario; Uder, Michael; Nagel, Armin Michael; Dahlmann, Anke (Kidney International Reports, 2024)
INTRODUCTION: Tissue Na+ overload is present in patients receiving hemodialysis (HD) and is associated with cardiovascular mortality. Strategies to actively modify tissue Na+ amount in these patients by adjusting the HD regimen have not been evaluated. METHODS: In several substudies, including cross-sectional analyses (n = 75 patients on HD), a cohort study and a cross-over interventional study (n = 10 patients each), we assessed the impact of ultrafiltration (UF) volume, prolongation of dialysis treatment time, and modification of dialysate Na+ concentration on tissue Na+ content using 23Na magnetic resonance imaging (23Na-MRI). RESULTS: In the cross-sectional analysis of our patients on HD, differences in dialysate sodium concentration ([Na+]) were associated with changes in tissue Na+ content, whereas neither UF volume nor HD treatment time affected tissue Na+ amount. Skin Na+ content was lower in 17 patients on HD, with dialysate [Na+] of <138 mmol/l compared to 58 patients dialyzing at ≥138 mmol/l (20.7 ± 7.3 vs. 26.0 ± 8.8 arbitrary units [a.u.], P < 0.05). In the cohort study, intraindividual prolongation of HD treatment time was not associated with a reduction in tissue Na+ content. Corresponding to the observational data, intraindividual modification of dialysate [Na+] from 138 to 142 to 135 mmol/l resulted in concordant changes in skin Na+ (24.3 ± 7.6 vs. 26.3 ± 8.0 vs. 20.8 ± 5.6 a.u, P < 0.05 each), whereas no significant change in muscle Na+ occurred. CONCLUSION: Solely adjustment of dialysate [Na+] had a reproducible impact on tissue Na+ content. 23Na-MRI could be utilized to monitor the effectiveness of dialysate [Na+] modifications in randomized-controlled outcome trials.
EVALuna2:568181

Na+ deposition in the fibrotic skin of systemic sclerosis patients detected by 23Na-magnetic resonance imaging - Kopp, Christoph; Beyer, Christian; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Neubert, Patrick; Rosenhauer, Daniela; Mueller, Dominik N.; Eckardt, Kai-Uwe; Schett, Georg; Luft, Friedrich C.; et al. (Rheumatology, 2017)
Skin fibrosis is the predominant feature of SSc and arises from excessive extracellular matrix deposition. Glycosaminoglycans are macromolecules of the extracellular matrix, which facilitate Na(+) accumulation in the skin. We used (23)Na-MRI to quantify Na(+) in skin. We hypothesized that skin Na(+) might accumulate in SSc and might be a biomarker for skin fibrosis.In this observational case-control study, skin Na(+) was determined by (23)Na-MRI using a Na(+) volume coil in 12 patients with diffuse cutaneous SSc and in 21 control subjects. We assessed skin fibrosis by the modified Rodnan skin score prior to (23)Na-MRI and on follow-up 12 months later.(23)Na-MRI demonstrated increased Na(+) in the fibrotic skin of SSc patients compared with skin from controls [mean (sd): 27.2 (5.6) vs 21.4 (5.3) mmol/l, P < 0.01]. Na(+) content was higher in fibrotic than in non-fibrotic SSc skin [26.2 (4.8) vs 19.2 (3.4) mmol/l, P < 0.01]. Furthermore, skin Na(+) amount was correlated with changes in follow-up modified Rodnan skin score (R(2) = 0.68).(23)Na-MRI detected increased Na(+) in the fibrotic SSc skin; high Na(+) content was associated with progressive skin disease. Our findings provide the first evidence that (23)Na-MRI might be a promising tool to assess skin Na(+) and thereby predict progression of skin fibrosis in SSc.
EVALuna:33997

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Skin Sodium Concentration Correlates with Left Ventricular Hypertrophy in CKD - Schneider, Markus P.; Raff, Ulrike; Kopp, Christoph; Scheppach, Johannes B.; Toncar, Sebastian; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Floege, Juergen; Schmid, Matthias; Birukov, Anna; Dahlmann, Anke; et al. (Journal of the American Society of Nephrology, 2017)
The pathogenesis of left ventricular hypertrophy in patients with CKD is incompletely understood. Sodium intake, which is usually assessed by measuring urinary sodium excretion, has been inconsistently linked with left ventricular hypertrophy. However, tissues such as skin and muscle may store sodium. Using (23)sodium-magnetic resonance imaging, a technique recently developed for the assessment of tissue sodium content in humans, we determined skin sodium content at the level of the calf in 99 patients with mild to moderate CKD (42 women; median [range] age, 65 [23-78] years). We also assessed total body overhydration (bioimpedance spectroscopy), 24-hour BP, and left ventricular mass (cardiac magnetic resonance imaging). Skin sodium content, but not total body overhydration, correlated with systolic BP (r=0.33, P=0.002). Moreover, skin sodium content correlated more strongly than total body overhydration did with left ventricular mass (r=0.56, P<0.001 versus r=0.35, P<0.001; P<0.01 between the two correlations). Linear regression analysis demonstrated that skin sodium content is a strong explanatory variable for left ventricular mass, unaffected by BP and total body overhydration. In conclusion, we found skin sodium content to be closely linked to left ventricular mass in patients with CKD. Interventions that reduce skin sodium content might improve cardiovascular outcomes in these patients.
EVALuna2:3863

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Two adjacent phosphorylation sites in the C-terminus of the channel’s α-subunit have opposing effects on epithelial sodium channel (ENaC) activity - Diakov, Alexei; Nesterov, Viatcheslav; Dahlmann, Anke; Korbmacher, Christoph (Pflügers Archiv: European Journal of Physiology, 2022)
How phosphorylation of the epithelial sodium channel (ENaC) contributes to its regulation is incompletely understood. Previously, we demonstrated that in outside-out patches ENaC activation by serum- and glucocorticoid-inducible kinase isoform 1 (SGK1) was abolished by mutating a serine residue in a putative SGK1 consensus motif RXRXX(S/T) in the channel’s α-subunit (S621 in rat). Interestingly, this serine residue is followed by a highly conserved proline residue rather than by a hydrophobic amino acid thought to be required for a functional SGK1 consensus motif according to invitro data. This suggests that this serine residue is a potential phosphorylation site for the dual-specificity tyrosine phosphorylated and regulated kinase 2 (DYRK2), a prototypical proline-directed kinase. Its phosphorylation may prime a highly conserved preceding serine residue (S617 in rat) to be phosphorylated by glycogen synthase kinase 3 β (GSK3β). Therefore, we investigated the effect of DYRK2 on ENaC activity in outside-out patches of Xenopus laevis oocytes heterologously expressing rat ENaC. DYRK2 included in the pipette solution significantly increased ENaC activity. In contrast, GSK3β had an inhibitory effect. Replacing S621 in αENaC with alanine (S621A) abolished the effects of both kinases. A S617A mutation reduced the inhibitory effect of GKS3β but did not prevent ENaC activation by DYRK2. Our findings suggest that phosphorylation of S621 activates ENaC and primes S617 for subsequent phosphorylation by GSK3β resulting in channel inhibition. In proof-of-concept experiments, we demonstrated that DYRK2 can also stimulate ENaC currents in microdissected mouse distal nephron, whereas GSK3β inhibits the currents.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Dual-specificity tyrosine phosphorylated and regulated kinase 2 (DYRK2); Epithelial sodium channel (ENaC); Glycogen synthase kinase 3 beta (GSK3β); Microdissected mouse distal nephron; Patch clamp; Serum- and glucocorticoid-induced kinase isoform 1 (SGK1); Xenopus laevis oocytes